Effects of Inquiry and the Ashmore Problem-Solving Model on Performance and Attitudes in Trigonometry Among Senior Secondary School Students in Rivers East Senatorial District, Nigeria - Adolphus, Telima; Nweke, Nwanne Okechukwu (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
The study investigated the effects of Inquiry-Based Learning (IBL) and the Ashmore Model on senior secondary school students’ performance and attitude toward trigonometry in Rivers State, Nigeria. A quasi-experimental pretest-posttest control group design was employed. A multistage sampling technique was used to select 398 SS2 students from six intact classes across six public senior secondary schools. Two instruments, the Trigonometry Performance Test (TPT; reliability = 0.73) and the Students’ Trigonometry Attitude Questionnaire (STAQ; α = 0.78), were used for data collection. Data were analyzed using mean, standard deviation, ANCOVA, and Bonferroni Post Hoc Pairwise Comparison at a 0.05 significance level. Results showed that students taught using IBL and the Ashmore model performed significantly better than those taught with the lecture method (F(2, 394) = 35.15, p < .001, η² = .151), with mean gains of 10.47 (IBL), 9.26 (Ashmore), and 4.10 (Lecture). Attitude scores also favored IBL (mean gain = 11.59) over Ashmore (9.24) and Lecture (5.51) groups (F(2, 394) = 41.89, p < .001, η² = .175). Although males slightly outperformed females in the IBL group and females outperformed males in the Ashmore group, gender differences were not statistically significant (F(1, 265) = 0.102, p = .750). The study recommends the use of interactive and inquiry-driven strategies to enhance students’ engagement, performance, and attitudes in trigonometry.